Pelaksanaan Pengawasan Notaris Yang Meninggalkan Wilayah Jabatan Tanpa Cuti Berdasarkan Undang-Undang Jabatan Notaris - Y, Dinda Nurfitria Putri (Al Makki Publisher, 2024)
A notary is a public official who has the main duties and functions of serving the public who use his services. In terms of his position, he has an office area where he can make authentic deeds and powers of attorney. A notary is prohibited from leaving his/her area of office. The method the author uses is normative juridical with a statutory approach and analyzes using descriptive methods. The result is that a notary who leaves the area of office without leave permission and the knowledge of the supervisor will be sentenced to administrative sanctions in the form of written or verbal warnings and the most fatal in the form of temporary dismissal or even dishonorable dismissal. Even though a notary has the right to leave after he has served for 2 years. There was no justifiable reason when he did not apply for leave and then left his area of office. Therefore, strict supervision is needed so that violations like this do not occur. This supervisory council, in carrying out its authority, is to supervise not only the implementation of the office of notary but also all the actions of a notary both in carrying out his official duties as well as in his daily life in order to create a professional notary in serving the legal needs of the community so that legal certainty can be created by the community. need.